Teaching of the Language in Colombia from a Glotopolitical Perspective - Cisneros Estupiñan, Mireya; Mahecha, Miguel Ángel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper presents glotopolitical reflections in relation to multilingualism and bilingualism in Colombia, as well as the characteristics of both sociolinguistic and glotopolitical approach. It also raises the need to implement in our country linguistic policy and planning based on glotopolitical criteria enabling equitable development of languages that are part of the social, cultural and everyday reality in Colombia.